AKTIVITAS ANTIOKSIDAN FRAKSI AIR DAN FRAKSI ETER KOMBINASI EKSTRAK METANOL DAUN KOPI ARABIKA (Coffea arabica L.) DAN KULIT BATANG KAYU MANIS (Cinnamomum burmannii Nees ex BI.): Antioxidant Activity of Water and Ether Fraction Combination of Arabica Coffee Leaves (Coffea arabica L.) Extract and Cinnamon burmanii Bark (Cinnamomum burmannii Nees ex Bi.) - Fauzan Arrozi; Retnaningtyas, Yuni; Wulandari, Lestyo (Universitas Tidar, 2023)
Antioxidants are compounds that can inhibit an oxidation reaction, by binding to free radicals that play a role in the emergence of several degenerative diseases. Arabica coffee (Coffea arabica) and cinnamon (Cinnamomum burmannii) are plants that have antioxidant activity so that when combined they have the potential to produce a synergistic effect. The purpose of this study was to test the antioxidant effects of the combination of methanol extract of Arabica coffee leaves and cinnamon bark in both the water and ether fractions. Antioxidant activity was determined using the DPPH method, as a positive control vitamin C was used, and antioxidant activity was expressed in the form of IC50. The results showed a synergistic effect of the two extracts where the antioxidant activity of both the water fraction and the ether fraction in the combined form was greater than the single form. The highest antioxidant activity was shown by the water fraction of the combination of methanol extract of Arabica coffee leaves and cinnamon bark in a ratio (1:2) with an IC50 value of 8.759 ± 0.050 g/mL. This antioxidant activity is lower than the antioxidant activity of vitamin C with an IC50 value of 3.267 ± 0.007 g/mL